Harris Hotel Bandung's Strategy in Providing Excellent Service for Guests - Syahwa Annisa Rachman; Widya Utami (An International Journal Tourism and Community Review, 2025)
This study aims to explore the strategies implemented by Harris Hotel Bandung in an effort to provide excellent service to guests. The background of this study is rooted in the importance of high service quality in the hospitality industry to increase guest satisfaction and loyalty. The method used is a qualitative approach, with data collection through in-depth interviews and direct observation at the hotel. The research results revealed that Harris Hotel Bandung implements various strategies, including regular employee training, utilization of technology to improve service efficiency, and a personal approach in interacting with guests. The hotel also pays special attention to guest feedback to continuously improve the services provided.